Development of Footwork Exercise Tool Based on Android for Badminton - Endang Sepdanius; Nindie Novselia (Universitas Negeri Medan, 2019)
The research purpose was to test the acceptance and the effectiveness of exercise tool in badminton. The kind of this research was Research and Development that was done in 6 steps: (1)Potential problems,(2)collecting information,(3)design,(4)validation,(5)design improvement,(6)product trial. Experts’ validations were done by badminton academic and coach. The subjects of this research were conducted to 68 subjects. The instruments in collecting data were tool acceptance questioner and the score that was gotten by using the tool. Technique of analyzing data used descriptive analysis technique. Results showed that the experts stated that the tool appropriate to used. 91.4% athletes received the tool. The effectiveness of tool was seen from the average score of lamps that live randomly were 19 times per minute. In conclusion, this training tool can be used for training facilities because it is effective in determining the intensity of training